Ледяная принцесса: [роман] / Т. А. Дубровина, Е. Н. Ласкарева - Дубровина Татьяна Артемьевна (Русский романс, 2003)
Экземпляры: ф.8 (2003) / Инвентарный номер: 46661 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Д 79 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44